2020
DOI: 10.21608/ejchem.2020.21510.2280
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis and characterization of gold nanoparticles with polyunsaturated oils contribute to hypolipidemic and anti-obesity activities in vivo.

Abstract: This study aimed to evaluate the hypolipidemic, and anti-obesity effects of polyunsaturated oils, mixed with gold nanoparticles (AuNPs). AuNPs were prepared by the oleic acid pyrolysis method. The sample was characterized by UV spectroscopy and transmission electron microscope (TEM). Sixty adult male rats were divided into 2 main groups. Group one (n=10 rats) was fed on the healthy diet (serves as basic control). The other group was fed on the high fructose diet (HFD) for four weeks and then was divided into f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
(53 reference statements)
0
0
0
Order By: Relevance
“…This study was performed to increase the HDL concentration in the blood circulation. In vivo study in the obese rat suggested that PUFAs and PUFAs incorporated AuNPs have increased ~1.2-and 1.6-fold-higher HDL, respectively, compared to the control group [107]. A new class of nanocarrier was developed by researchers with antioxidant polymer cores, while the outer layer was decorated with scavenger receptors targeting amphiphilic macromolecules.…”
Section: Anti-hyperlipidemic Nanomedicinesmentioning
confidence: 99%
“…This study was performed to increase the HDL concentration in the blood circulation. In vivo study in the obese rat suggested that PUFAs and PUFAs incorporated AuNPs have increased ~1.2-and 1.6-fold-higher HDL, respectively, compared to the control group [107]. A new class of nanocarrier was developed by researchers with antioxidant polymer cores, while the outer layer was decorated with scavenger receptors targeting amphiphilic macromolecules.…”
Section: Anti-hyperlipidemic Nanomedicinesmentioning
confidence: 99%